Perceptions of Assistive Technology by Teachers of Students with Visual Impairments in Jordan. (November 2020) - Al-Zboon, Eman
Introduction: Ethical practices and technology are current trends in education for individuals with disabilities. This study investigates the perceptions of assistive technology expressed by teachers of students with visual impairments (i.e., blindness or low vision) in Jordan. Methods: The research involved 20 teachers. Data were collected via semistructured interviews and analysis carried out via the constant-comparative method. Results: The results highlight the challenges that teachers perceive in using assistive technology with their students, particularly regarding computer use, the willingness of a child to use a particular device, the lack of such technologies in schools and in the home, and a lack of training in the home. The results highlight perceived external barriers to the effective use of assistive technology, including those related to finance, training, societal attitudes, and family support. It appears that assistive technology can also have negative effects, which can be considered an ethical issue, since such technologies can expose students with visual impairments to negative community attitudes, addiction, bullying, abuse, and extremism. Discussion: Teachers highlight the issues they experience in using assistive technology with students with visual impairments in Jordan, which can be explained by the contextual conditions in the country. Implications for practitioners: Decision-makers in the field of visual impairment need to consider these issues through providing professional development, addressing financial barriers, and conducting awareness programs for students regarding the effective use of assistive technology.